Post-hydrothermal treatment of hydrothermal electrodeposited CaHPO4 on C/C composites in sodium silicate-containing solution at various temperatures. Issue 5 (1st April 2019) - Ling, Liu; Xin-bo, Xiong; Jun, Ma; Xin-ye, Ni; Xie-rong, Zeng; Sial, Muhammad Aurang Zeb Gul; Dazhu, Chen
Abstract: Direct deposition of hydroxyapatite (HA) coatings on carbon/carbon(C/C) composites through hydrothermal electrochemical deposition (HED) were limited by the poor bonding strength. To overcome this problem，in this work, CaHPO4 (monetite) coating was firstly deposited on C/C using HED, and then converted into HA coating in a sodium silicate–containing solution by post-hydrothermal treatment. Effects of post-treatment temperatures on the chemical composition, structure, and bonding strength of the coatings were investigated. The results showed that obtained monetite showed a compact microstructure, and could react with the solution to produce a well-crystallized HA as well as amorphous silicate which contained some calcium and sodium ions. All the coatings were composed of rod-like crystals. The diameter of these crystals increased when the post-hydrothermal temperature was changed from 110 ℃ to 140 ℃, and then decreased at 155 ℃. The Si contents and the adhesive strength of the HA coatings showed a similar temperature dependence to the crystal size of the HA. 140 ℃ is determined to the optimal treatment temperature, at which the HA coating reached the highest critical load of 24.02 N, corresponding to the shear strength of 82.83 MPa. The bioactivity of the HA coating on C/C increased with the increasing post-treatment temperature.